Islamic Philanthropic Fund Management: The Role Of Infaq And Sadaqah In Supporting Infrastructure Development At Annuqayah - M Ulul Azmi Iwan; Umarul Faruq; Mitha Endah Aprilia (Asian Journal of Law and Islamic Finance, 2025)
Islamic boarding schools (pesantren) in Indonesia face significant challenges in infrastructure development due to limited government funding, necessitating alternative financing methods. This study examines the management practices of infaq and sadaqah funds at Pondok Pesantren Annuqayah Daerah As-Syafiiyah and their role in supporting infrastructure development. The research employed a qualitative approach with a case study design, collecting data through in-depth interviews with 15 key informants, direct observation of development activities, and document analysis of financial and project records. The study reveals a systematic management approach incorporating four key functions—planning, organizing, implementing, and monitoring—adapted to accommodate religious values and local cultural contexts. Infaq and sadaqah funds contribute significantly to infrastructure development through educational facility funding, supporting infrastructure enhancement, maintenance programming, and financial independence promotion. This has enabled substantial physical expansion, including dormitory facilities that increased student capacity from 45 to 200 students between 2022-2024. The research concludes that effective management of Islamic philanthropic funds requires balancing religious authenticity with operational effectiveness through adaptive planning systems, transparent accountability mechanisms, and knowledge transfer procedures. These findings offer practical implications for similar institutions seeking sustainable financing alternatives and suggest that further research should explore comparative approaches across different pesantren contexts to develop generalizable principles for Islamic philanthropic fund management in educational settings.